1998
DOI: 10.1128/aac.42.4.827
|View full text |Cite
|
Sign up to set email alerts
|

Cefotaxime-Resistant Enterobacteriaceae Isolates from a Hospital in Warsaw, Poland: Identification of a New CTX-M-3 Cefotaxime-Hydrolyzing β-Lactamase That Is Closely Related to the CTX-M-1/MEN-1 Enzyme

Abstract: A group of cefotaxime-resistant Citrobacter freundiiand Escherichia coli isolates were collected by a clinical laboratory in a hospital in Warsaw, Poland, in July 1996. Detailed analysis has shown that all of these produced a β-lactamase (pI, 8.4) belonging to the CTX-M family, one of the minor extended-spectrum β-lactamase families with a strong cefotaxime-hydrolyzing activity. Sequencing has revealed that C. freundii isolates produced a new CTX-M-3 enzyme which is very closely related to the CTX-M-1/MEN-1 β-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(52 citation statements)
references
References 18 publications
(32 reference statements)
2
49
0
Order By: Relevance
“…1-4 CTX-M-3 is among the most common ESBLs in Polish hospitals. 4,5 Sporadic enterobacterial isolates producing CTX-M-3 have also been reported in France and Taiwan. 6,7 Recently, we showed the spread of a CTX-M-4-producing Salmonella typhimurium clone in Russia, Hungary, and Greece.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…1-4 CTX-M-3 is among the most common ESBLs in Polish hospitals. 4,5 Sporadic enterobacterial isolates producing CTX-M-3 have also been reported in France and Taiwan. 6,7 Recently, we showed the spread of a CTX-M-4-producing Salmonella typhimurium clone in Russia, Hungary, and Greece.…”
Section: Resultsmentioning
confidence: 94%
“…Sequencing of PCR products using purified pT27 as template showed that the detected CTX-M gene was identical with bla CTX-M-3 . 4 Comparison of plasmid pT27 with p3291, a plasmid carrying the prototype bla CTXM-3 4 (kindly provided by Marek Gniadkowski, Sera and Vaccines Research Laboratory, Warsaw, Poland), by endonuclease restriction analysis did not reveal any significant similarity. Quantitative differences in susceptibility to b-lactam antibiotics were observed when these plasmids were introduced into the same host.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 ArmA was first identified in an isolate of K pneumoniae from the urine of a patient admitted to a hospital in Paris in 2000, 7 but its nucleotide sequence could be found on a plasmid carried by a Citrobacter freundii clinical strain identified in Poland in 1996. 9,10 ArmA was subsequently confirmed to function as N7-G1405 16S-RMTase. 11 RmtA was identified in a sputum isolate of P aeruginosa in Japan in 1997.…”
Section: Acquired 16s Ribosomal Rna Methyltransferases In Gram-negatimentioning
confidence: 90%
“…Shortly after that, Bauernfeind et al (1989) reported on a clinical cefotaxime-resistant E. coli strain in Germany which produced a CTX-M-1 type beta-lactamase. In the following 10 years several studies reported about an explosive dissemination of ESBLs in human clinical settings worldwide (Bernard et al, 1992; Gniadkowski et al, 1998; Radice et al, 2002; Canton and Coque, 2006). Several review articles provide detailed insight into the occurrence and molecular epidemiology of ESBL producing Enterobacteriaceae in humans and animals (Bradford, 2001; Bonnet, 2004; Canton and Coque, 2006; Livermore et al, 2007; Cantón et al, 2008; Oteo et al, 2010; Pfeifer et al, 2010; Pitout, 2010; Wieler et al, 2011).…”
Section: Introductionmentioning
confidence: 99%